A model development of relationships between tourism experiences - de Matos, Nelson (2012)
The latest economic downturn raises new predicaments for DMO’s and stakeholders to meet their target’s needs, but it also takes to the forefront of the tourism industry the importance to assess how the tourism experiences impact on the tourists’ perceived destination image, to prevent money being loss in the wrong promotion strategies. This paper purpose is twofold: A) to review the destination image and tourism experiences constructs; B) to develop a theoretical model between the experiences and the destination image.